2011
DOI: 10.1158/1535-7163.mct-10-0568
|View full text |Cite
|
Sign up to set email alerts
|

Silencing of Tubulin Binding Cofactor C Modifies Microtubule Dynamics and Cell Cycle Distribution and Enhances Sensitivity to Gemcitabine in Breast Cancer Cells

Abstract: Tubulin binding cofactor C (TBCC) is essential for the proper folding of a-and b-tubulins into microtubule polymerizable heterodimers. Because microtubules are considered major targets in the treatment of breast cancer, we investigated the influence of TBCC silencing on tubulin pools, microtubule dynamics, and cell cycle distribution of breast cancer cells by developing a variant MCF7 cells with reduced content of TBCC (MCÀ). MCÀ cells displayed decreased content in nonpolymerizable tubulins and increased cont… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…A previous study showed that modulation of microtubule dynamics by the silencing of tubulin binding cofactor C and cell cycle distribution enhanced the sensitivity to gemcitabine in breast cancer cells. 39 Furthermore, the combination of the benzophenone analogue S516, which changed the cellular microtubule network, with gemcitabine significantly delayed the growth of lung cancer tumours as compared with control and gemcitabine alone. 40…”
Section: Discussionmentioning
confidence: 98%
“…A previous study showed that modulation of microtubule dynamics by the silencing of tubulin binding cofactor C and cell cycle distribution enhanced the sensitivity to gemcitabine in breast cancer cells. 39 Furthermore, the combination of the benzophenone analogue S516, which changed the cellular microtubule network, with gemcitabine significantly delayed the growth of lung cancer tumours as compared with control and gemcitabine alone. 40…”
Section: Discussionmentioning
confidence: 98%
“…TBCA is a member of a family of proteins that act at different levels of a folding pathway to generate tubulin heterodimers involved in many cellular functions. As two independent studies have reported a role for these chaperones in the sensitivity/resistance to treatment of different types of cancer [57,58], the similarity of S100A4 and TBCA profiles in rat spleen in the context of MM progression is intriguing. The additional data on ANXA2 finally suggest that markers of communication between cells/intracellular transport, cell motility, and cellular architecture are closely interconnected, especially in the more advanced stages, highlighting the key role of the S100A4/annexin A2 interaction [59].…”
Section: Discussionmentioning
confidence: 99%
“…Given the importance of MTs in cell division and the widely accepted concept that cancer cells divide more rapidly than normal cells, it has been generally assumed that MTAs mediate cytotoxicity by interfering with mitosis (1, 2). Elegant in vitro and preclinical data have demonstrated time and again that MTAs lead to mitotic arrest and in turn cell death (5,(7)(8)(9)(10)(11)(12). Arrest in mitosis as the mechanism that leads to cell death is possible in these preclinical models because their doubling times range from a few hours to at most a few days, and even brief drug exposures are likely to encounter a substantial fraction of cells traversing through mitosis.…”
Section: Discussionmentioning
confidence: 99%